Slo1 Tail Domains, but Not the Ca(2+) Bowl, Are Required for the β1 Subunit to Increase the Apparent Ca(2+) Sensitivity of BK Channels - Qian, Xiang (The Rockefeller University Press, 2002)
Functional large-conductance Ca(2+)- and voltage-activated K(+) (BK) channels can be assembled from four α subunits (Slo1) alone, or together with four auxiliary β1 subunits to greatly increase the apparent Ca(2+) sensitivity of the channel. We examined the structural features involved in this modulation with two types of experiments. In the first, the tail domain of the α subunit, which includes the RCK2 (regulator of K(+) conductance) domain and Ca(2+) bowl, was replaced with the tail domain of Slo3, a BK-related channel that lacks both a Ca(2+) bowl and high affinity Ca(2+) sensitivity. In the second, the Ca(2+) bowl was disrupted by mutations that greatly reduce the apparent Ca(2+) sensitivity. We found that the β1 subunit increased the apparent Ca(2+) sensitivity of Slo1 channels, independently of whether the α subunits were expressed as separate cores (S0-S8) and tails (S9-S10) or full length, and this increase was still observed after the Ca(2+) bowl was mutated. In contrast, β1 subunits no longer increased Ca(2+) sensitivity when Slo1 tails were replaced by Slo3 tails. The β1 subunits were still functionally coupled to channels with Slo3 tails, as DHS-I and 17 β-estradiol activated these channels in the presence of β1 subunits, but not in their absence. These findings indicate that the increase in apparent Ca(2+) sensitivity induced by the β1 subunit does not require either the Ca(2+) bowl or the linker between the RCK1 and RCK2 domains, and that Slo3 tails cannot substitute for Slo1 tails. The β1 subunit also induced a decrease in voltage sensitivity that occurred with either Slo1 or Slo3 tails. In contrast, the β1 subunit–induced increase in apparent Ca(2+) sensitivity required Slo1 tails. This suggests that the allosteric activation pathways for these two types of actions of the β1 subunit may be different.